Influence of Sweet Corn Seed Vigors on Yield and Optimum Seeding Rate - Supot Faungfupong; Juangjun Duangpatra; Gunching Siriwitayawan; Surapolg Choachong (Agriculture and Natural Resources, 1993)
Works con fisted of two parts. Seeds of sweet corn variety Thai Super Sweet Composite DMR#1 were pretreated in the aboratory in order to obtain three vigor levels of seeds namely high (86-100% germination), medium (76-85% germination) and low 65-75% germination). These seeds were then field-tested at the National Corn and Sorghum Research Center during August-October of 1990 using a split plot design. Five seeding methods were the main plot and three levels of seed vigor as the sub-plot. The identical experiments were carried out under both irrigation and rainfed conditions. The results showed the superiority of using high vigor seed to those of medium and low vigor seeds respectively on stand establishment, plant growth and sweet corn yield. It was recommended that farmers should adopted high vigor seed for planting and without over-planting of seed. For medium and low vigor seeds 1.5 and 2.0 times greater than the desirable plant numbers of seed should be dropped at planting.